QTc interval in anorexia nervosa: a systematic review and meta-analysis. (3rd October 2022) - Rastogi, J; Ho, J; Rastogi, J; Lazari, J; Jageer, P; Davis, S; Kirresh, A; Yiu, J; Jain, D; Ahmad, M; Providencia, R; Bray, J
Abstract: Background: Patients with anorexia nervosa (AN) are at higher risk of sudden cardiac death. Although the underlying aetiology for this association remains unclear. It may be related to prolongation of the QT interval, which can degenerate into fatal ventricular arrhythmias. However, the presence of prolonged heart rate-corrected QT interval (QTc) in AN remains controversial, and two previous meta-analyses on AN and QTc showed contradictory findings [1, 2]. Purpose: In this systematic review and meta-analysis, we aimed to evaluate if AN was associated with changes in the QTc interval and dispersion. Methods: MEDLINE, EMBASE and COCHRANE databases were systematically searched from inception to January 2021. Random-effects meta-analysis and meta-regression were used. The inclusion criteria were (i) confirmed diagnosis of AN, (ii) measurement of QTc on electrocardiogram and (iii) peer-reviewed articles. The primary endpoint of the study was the duration of the QTc interval calculated using the Bazett (QTcB), Hodges (QTcH), Fridericia (QTcF) and Framingham (QTcFr) formulae. The secondary endpoints were QT dispersion (QTd) and QTc dispersion (QTcd). Results: The 25 eligible studies included 5687 patients (1862 AN, 3825 control) (Figure 1: PRISMA diagram). The majority of patients were female (96.3%) with a mean age between 14.3 to 31.0 years and mean duration of disease ranging from 9.1 to 129.6 months. The mean BMI ranged from 13.7 to 18.5 kg/m 2 . Pooled analysis did not show significant prolongation between AN versus control in QTcB (mean difference (MD) MD 4.9ms, 95% CI −3.2, 13.1ms, p=0.23; I 2 =95%; n=24/25 studies; Figure 2A), QTcH (MD 1.3ms, 95% CI −8.5, 11.2ms, p=0.79; I 2 =71%; n=3/25 studies), and QTcF (MD 3.1ms, 95% CI −21.6, 27.7ms, p=0.81; I 2 =97%; n=3/25 studies). Only two studies reporting QTcFr showed a significant prolongation between AN and control (MD 15.9ms, 95% CI 0.0, 31.8ms, p=0.05, I 2 =65%; n=2/25 studies; Figure 2B). However, QTd and QTcd were significantly greater in AN than control (MD 21.3ms, 95% CI 10.4, 32.3ms, p=0.0001, I 2 =94%; Figure 2C and MD 16.9ms, 95% CI 4.5, 29.3ms, p=0.007 I 2 =93%; Figure 2D, respectively). Conclusion: To the best of our knowledge, this is the largest meta-analysis of QTc in AN and the first meta-analysis exploring the significance of QTd and QTcd in AN. AN was not found to be associated with prolongation of QTc calculated using the Bazett, Fridericia and Hodges formulae. However, an association of AN with prolonged QTc was observed in the studies using the Framingham formula. More pronounced dispersion (QTd and QTcd) was also observed in patients with AN. Funding Acknowledgement: Type of funding sources: None.